Factor V Leiden, FII G20210A, MTHFR C677T mutations as risk factors for venous thrombosis during pregnancy and puerperium - Đorđević Valentina; Rakićević Ljiljana B.; Spasić Miloš; Miljić Predrag; Miković Danijela; Kovač Mirjana; Radojković Dragica (Vojnosanitetski Pregled, 2005)
Background. Venous thrombosis is the most common cause of obstetric morbidity and mortality during pregnancy and puerperium. The incidence of pregnancy associated venous thrombosis varies from 1 in 1000 to 1 in 2000 deliveries. Factor V G1691A (FV Leiden), FII G20210A and MTHFR C677T mutations are the most common genetic risk factors for thromboembolism. The aim of this study was to establish the presence of these risk factors in a group of women with an episode of deep venous thrombosis during pregnancy or puerperium. Methods. The study was carried in a group of 45 women with the first episode of deep venous thrombosis during pregnancy or puerperium. The patients with antiphospholipid antibodies, antithrombin III, protein C or protein S deficiency, and autoimmune and malignant diseases were excluded from the study. FV Leiden, FII G20210A, and MTHFR C677T mutations were detected by polymerase chain reaction, followed by digestion with specific restriction enzymes. Results. Twenty heterozygous carriers of the FV Leiden mutation and one homozygous carrier were detected, which represents the frequencies of 44.4% and 2.2%, respectively. For the FII G20210A mutation, six heterozygous carriers were identified, giving the frequency of 13.3%. The MTHFR C677T mutation was observed in 31 patients (22 heterozygous and 9 homozygous carriers) which represents the frequencies of 48.9% and 20%, respectively. Conclusion. Our study suggested that the obligatory testing for FV Leiden and FII G20210A mutations was strongly recommended in women with history of venous thrombosis during pregnancy and puerperium. We found a slight effect of MTHFR 677T allele, but it should be considered in association with other risk factors.